2020
DOI: 10.1016/j.forsciint.2020.110343
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning in drug addicts in the Nordic countries in 2017

Abstract: This study is the seventh report on fatal poisonings among drug addicts in the Nordic countries. In this report, we analyse data from the five Nordic countries: Denmark, Finland, Iceland, Norway and Sweden. Data on gender, number of deaths, places of deaths, age, main intoxicants and substances detected in blood were recorded to obtain national and comparable Nordic data, and to allow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 13 publications
2
53
1
5
Order By: Relevance
“…Finland has an opioid abuse profile different from the neighboring Nordic countries, with a very limited supply of heroin and less methadone abuse. Buprenorphine accounts for about one third of the total drug poisoning mortality (5.84 per 100,000 for inhabitants aged 15-64 in 2017) (Simonsen et al, 2020). Uosukainen et al studied clients seeking treatment for buprenorphine abuse and found that daily buprenorphine abuse, intravenous administration, and concurrent substance use were common (Uosukainen et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Finland has an opioid abuse profile different from the neighboring Nordic countries, with a very limited supply of heroin and less methadone abuse. Buprenorphine accounts for about one third of the total drug poisoning mortality (5.84 per 100,000 for inhabitants aged 15-64 in 2017) (Simonsen et al, 2020). Uosukainen et al studied clients seeking treatment for buprenorphine abuse and found that daily buprenorphine abuse, intravenous administration, and concurrent substance use were common (Uosukainen et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of overdose deaths in five north European countries showed that the median number of detected drugs per case varied from 4 to 6. Opioids were the main cause of death but as well as heroin/ morphine, included methadone, buprenorphine and fentanyl analogues (Simonsen et al, 2020). Similarly, the analysis of a Finnish national post-mortem toxicology database showed that there were no death cases with buprenorphine as the only toxicological finding, with concomitant benzodiazepines commonly detected (Mariottini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the recreational use of opioids is not common in Norway, the relative number of opioid-related fatalities is higher than in most other European countries. The main cause of opioid overdoses used to be heroin, but in recent years the numbers of fatal overdoses by oxycodone, methadone, and buprenorphine has increased (Simonsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%